MODELLING OF EMERGENCY OPERATION IN ELECTRIC NETWORKS FEEDING RAILROAD TRACTION SUBSTATIONS - V. P. Zakaryukin; A. V. Kryukov; E. A. Alekseenko (Известия высших учебных заведений: Проблемы энергетики)
The methods and algorithms providing modeling of emergency operation are necessary for the solution of designing and operation of railway power supply systems of alternating current. These methods shall meet the following requirements: modeling adequacy and accuracy; result’s reliability; universality.